PENGARUH LEADER MEMBER EXCHANGE TERHADAP MOTIVASI, KEPUASAN KERJA DAN KOMITMEN ORGANISASI - Nopriyati (MNJ 16 UMY 234, 2016)
This study aims to analyze the influence of Leader member exchange of the motivation, job satisfaction and organizational commitment in PT. MONTAIGNE FURNITURE. The subjects in this study were employees of the field at PT. MONTAIGNE FURNITURE in Jepara. In this study sample of 132 respondents were chosen by population. The analysis tool used is SEM (Structural Equation Modeling). Based on the analysis that have been made the results are The leader member exchange no significant to the job satisfaction, motivation, and organizational commitment, motivation is not significant to organizational comitment, motivation significant on job satisfaction and job satisfaction significant to organizational commitment. Keywords: Leader Member Exchange, Job Satisfaction, Motivation, and Organizational Commitment